Evaluation of bone and kidney toxicity of BT2-peg2, a potential carrier for the targeted delivery of antibiotics to bone. (2021) - Albayati, Zaineb A.F.; Penthala, Narsimha R.; Bommagani, Shobanbabu; Post, Ginell R.; Smeltzer, Mark S.; Crooks, Peter A.
Graphical abstract: Abstract: Previous studies have demonstrated that the bone targeting agent BT2-peg2 (BT2-minipeg2, 9 ), when conjugated to vancomycin and delivered systemically by intravenous (IV) or intraperitoneal (IP) injection accumulates in bone to a greater degree than vancomycin alone, but that this accumulation is associated with severe nephrotoxicity. To determine whether this nephrotoxicity could be attributed to BT2-peg2 itself, we used a rat model to assess the distribution and toxicity of BT2-peg2 after IP injection of 11 mg/kg twice daily for 21 days. The results demonstrated that BT2-peg2 accumulates in bone but there was no evidence of nephrotoxicity or any histopathological abnormalities in the bone. This suggests the nephrotoxicity observed in previous studies is likely due to the altered pharmacokinetics of vancomycin when conjugated to BT2-peg2 rather than to BT2-peg2 itself. Thus, BT2-peg2 may be a safe carrier for the enhanced delivery of antibiotics other than vancomycin to the bone as a means of combating bone infection. However, the data also emphasizes the need to carefully examine the pharmacokinetic characteristics of any BT2-peg2-antibiotic conjugate utilized for treatment of bone infections.